The Diabolic - Kincaid, S. J. (New York : Simon & Schuster BFYR, 2016)
Nemesis is a Diabolic, a humanoid teenager and the galaxys most deadly weapon, who masquerades as Sidonia, a senators daughter, and becomes a hostage of the galactic court.
Growing up alongside Sidonia, a galactic senators daughter she was created to protect, Nemesis is forced to disguise herself as Sidonia when a mad emperor attempts to thwart a rebellion against his corrupt forces.
Keywords: Courts and courtiers -- Fiction